HUBUNGAN METODE PEMBIASAAN DALAM PEMBELAJARAN DENGAN DISIPLIN ANAK USIA DINI - Nurul Ihsani; Nina Kurniah; Anni Suprapti (Universitas Bengkulu, 2018)
This study aims to describe the relationship between methods of habituation in learning with early childhood discipline in early childhood Al-Hidayah Kota Bengkulu. The method used is descriptive quantitative with correlation type. The subjects were 30 children consisting of 8 children of B1 group, 8 children of B2 group, 7 children of B3 group and 7 children of B4 group. Technique of collecting data using observation in the form of checklist. Data analysis using Product Moment Correlation. The result of this research is there is significant correlation between method of habituation in learning with discipline of child and seen from price Fhitung0,418 bigger than price Ftabel0,374 for significant level 5% (0,418 <0,374) so that Ha accepted and Ho rejected. Based on these results it is advisable to train early childhood discipline should teachers apply methods of habituation.Keywords: Method of Habituation in Learning, Discipline of Early Childhood